2020
DOI: 10.1177/0145445520908509
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Research on the Manipulation of Response Effort in Applied Behavior Analysis

Abstract: Response effort refers to the distance, force/pressure, or number of discrete behaviors required to engage in a response. In applied behavior analysis, response effort has been used as an independent variable to address a variety of target responses. In this manuscript, we summarize recent clinical and organizational studies in which response effort was manipulated to increase a desirable behavior or decrease a problematic behavior. Recent clinical applications include the manipulation of response effort to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Underlying gamification presents perceived effort reduction by enhancing reward and reinforcement while pursuing a goal in a fun and engaging way [26]. Subsequently, a recent review [27] has shown that clinical applications that reduce the effort required from participants to engage in a desired response decrease self-injurious behavior, decrease pica, and increase appropriate eating.…”
Section: Existing Literature On Effort Reductionmentioning
confidence: 99%
“…Underlying gamification presents perceived effort reduction by enhancing reward and reinforcement while pursuing a goal in a fun and engaging way [26]. Subsequently, a recent review [27] has shown that clinical applications that reduce the effort required from participants to engage in a desired response decrease self-injurious behavior, decrease pica, and increase appropriate eating.…”
Section: Existing Literature On Effort Reductionmentioning
confidence: 99%
“…When tangible rewards are applied, students may mitigate the effects of the contingency by obtaining rewards a) when classmates share their rewards, b) by stealing them from classmates, and c) by procuring the tangible rewards and bringing them to school (Richardson et al, 2021). When students can gain access to rewards via lower effort behaviors, the contingency targeting higher effort behaviors (e.g., assignment performance) may be less effective (Friman & Poling, 1995; Neef et al, 1994; Wilder et al, 2021). Thus, these countercontrol behaviors may punish teachers’ behaviors by reducing the effectiveness of their independent group‐oriented rewards.…”
Section: Independent Group‐oriented Rewards: Typical Proceduresmentioning
confidence: 99%
“…When students can perform well enough to meet academic criteria but do not perform to criteria because meeting those criteria requires too much effort, there is an imbalance between reward strength and effort (Cates & Skinner, 2000; Neef et al, 1994; Wilder et al, 2021). To address this imbalance educators can reduce the effort to perform to criteria or strengthen rewards (Skinner, 2002).…”
Section: Independent Group‐oriented Rewards: Typical Proceduresmentioning
confidence: 99%
“…A similar review by Carr et al (1999) found that measurement of treatment acceptability among empirical studies published in JABA increased after the 1970s from 0 to 10%, reached a peak of 30% in the 1980s, and stabilized at about 16% in the late 1990s. More recently, systematic reviews have continued to emphasize the lack of social validity reporting in a range of intervention studies (Meindl et al, 2019;Wilder et al, 2020). Kennedy (1992) found that 54% of articles containing a social validity measure focused on the social validity of the effects of the behavior change programs, 25% focused on the social validity of the goals, and 22% focused on the social validity of the procedures.…”
Section: Introductionmentioning
confidence: 99%
“…(1999) found that measurement of treatment acceptability among empirical studies published in JABA increased after the 1970s from 0 to 10%, reached a peak of 30% in the 1980s, and stabilized at about 16% in the late 1990s. More recently, systematic reviews have continued to emphasize the lack of social validity reporting in a range of intervention studies (Meindl et al., 2019; Wilder et al., 2020).…”
Section: Introductionmentioning
confidence: 99%